A minimal inverse seesaw model with S4 flavour symmetry - Bikash Thapa; Sunita Barman; Sompriti Bora; N. K. Francis (Journal of High Energy Physics, 2023)
Abstract We construct an S 4 flavour symmetric minimal inverse seesaw model where the standard model is extended by adding two right-handed and two standard model gauge singlet neutrinos to explain the origin of tiny neutrino masses. The resulting model describes the lepton mass spectra and flavour mixing quite well for the case of the normal hierarchy of neutrino masses. The prediction of the model on the Dirac CP-violating phase is centered around 370.087°. Furthermore, using the allowed region for the model parameters, we have calculated the value of the effective Majorana neutrino mass, |〈m ee 〉|, which characterizes neutrinoless double beta decay.